Can ICT help Cambodian students become the solution for improving education in the country? - Corrado, Riccardo; Flinn, Robert E.; Tungjan, Patchanee (Journal of Management, Economics, and Industrial Organization, 2019)
We are entering the fourth industrial revolution and Cambodia needs to be ready. Technologies are changing not only the way we do things but our entire life. One of the spheres affected by this revolution is Education. “Education is the movement from darkness to light”, said Professor Allan Bloom, and Cambodia is still in the shadow. The low percentage of its Gross Domestic Product (GDP) doesn’t provide enough resources to all the schools and the young generations are affected by this. But, can Cambodia try to resolve this problem beginning from the resources it already has? Recognized theories and researches proofed the effectiveness of learning by teaching, so why Cambodia doesn’t use this as a resource and an opportunity? ICT can change and it is already changing education, and with the help of students, it can make the difference in the country. In this paper, we provide an overview of the education within the country, and we analyze the possibilities and issues that Cambodia can have and would face along the way of preparing itself for the fourth industrial revolution.